The impact of digital trade rules on the export-embodied carbon emissions - Liu, Sujuan; Gao, Yiyao (Frontiers in Environmental Science, 2025)
IntroductionThe synergistic development of digitalisation and environmental protection is an important issue in the context of global economic development. The core issue that needs to be addressed is whether digital trade rules can reduce the export embodied carbon emissions and what the specific mechanisms are.MethodUsing regional trade agreements (RTA) and bilateral trade data signed and implemented by 137economies from 2001 to2021, this paper quantifies the depth of digital trade rules from three aspects: total depth, core depth and enforce depth, based on the classification of digital trade rules in the TAPED database. Subsequently, by using the extended structural gravity model and adopting the PPML estimation method, the influence effect and mechanism of digital trade rules on the export-embodied carbon emissions at the production and consumption sides in RTA were explored.Results(1) The deepening of digital trade rules can significantly reduce the intensity of implied carbon emissions from exports at both the production and consumption sides; the effect on implied carbon emissions at the consumption side is greater than at the production side. (2) Mechanism analysis shows that the effects of technological innovation, cost reduction, shortening regulatory distances and bilateral value chain correlation are important mechanisms in the impact of digital trade rules on export embodied carbon emission intensity. (3) Heterogeneity analysis shows that trade promotion provisions have the strongest effect on export-related carbon emissions, followed by data management provisions. Intellectual property protection provisions have the weakest effect. Bilateral agreements, US templates, exports to developed countries and green products in digital trade rules have a greater inhibitory effect on carbon emissions. The study proposes policy recommendations to promote the adoption of high-level digital trade rules and reduce carbon emissions from trade.